Performance evaluation of novel tapered shell and tube cascaded latent heat thermal energy storage. (15th January 2021) - Rudra Murthy, B.V.; Nidhul, Kottayat; Gumtapure, Veershetty
Graphical abstract: Highlights: Thermal characterisation of PCMs using differential scanning calorimetry. Impact of natural convection in the PCM melting rate. The mean power of tapered unit is higher than cylindrical type CLHS unit. Higher melting rate in tapered CLHS unit with complete melting at bottom without fins. Abstract: Geometric design of the storage system plays a vital role in the enhancement of heat transfer rate and thereby in the advancement of latent heat thermal energy storage (LHTES) technology. The present study numerically compares the heat transfer performance of tapered type shell and tube cascaded latent heat storage (CLHS) model with that of the conventional cylindrical CLHS model with special emphasis on melting rate at the slowest melting portions (bottom) of the shell and tube unit. Thermal properties like transition temperature, latent, and specific heat of the three organic PCMs OM 42, OM 46, and OM 48 have been obtained using differential scanning calorimetry (DSC), and the same is employed in the 2-D numerical simulation carried out using enthalpy-porosity method. Tapered CLHS unit exhibited superior performance owing to stronger natural convective currents demonstrated via streamlines, velocity, temperature and mass fraction contours. In tapered unit, 17.6% higher mean power is obtained for same volume of PCMs in cylindrical unit. In contrast, the mean power of the discharging process for a tapered type is 2.4% lesser than cylindrical type CLHS. The outcomes highlight that the tapered type CLHS model utilizes convective heat transfer, effectively enhancing the melting rate of PCM without any additional structural configurations such as fins. Hence is also economically justifiable for higher energy storage for the same volume compared to conventional cylindrical CLHS units.